A Greener, Efficient Approach to Michael Addition of Barbituric Acid to Nitroalkene in Aqueous Diethylamine Medium - Al-Najjar, Hany; Barakat, Assem; Al-Majid, Abdullah; Mabkhot, Yahia; Weber, Manuel; Ghabbour, Hazem; Fun, Hoong-Kun (Molecules (Basel, Switzerland), 2014)
An efficient method for the synthesis of a variety of pyrimidine derivatives 3a–t by reaction of barbituric acids 1a,b as Michael donor with nitroalkenes 2a–k as Michael acceptor using an aqueous medium and diethylamine is described. This 1,4-addition strategy offers several advantages, such as using an economic and environmentally benign reaction media, high yields, versatility, and shorter reaction times. The synthesized compounds were identified by 1H-NMR, 13C-NMR, CHN, IR, and MS. The structure of compound 3a was further confirmed by single crystal X-ray structure determination.